DEVELOPMENT OF CARDBOARD FROM RECYCLED PAPER. - Reyna M., Leoncio (2003)
Tests have been conducted for paperboard from waste paper. The concentrations by weight of waste paper was 0.5%, O. 7%, 1% and 2%. The board obtained was tested for tensile strength. The results indicate that the yield strength decreases with the pulp concentration whereas rupture length erratic behavior.